Public Expenditure Review for Peru : Spending for Results - World Bank (Washington, DC, 2013)
The purpose of this Public Expenditure Review (PER) is to take stock of Peru's public expenditure since the last PER and identify the main challenges. The key underlying questions addressed are: (i) How did Peru's public expenditure and revenues develop over the past decade? (ii) How have decentralization and the shift towards results-based budgeting impacted this development across levels of government and sectors? And, (iii) to what extent are public expenditures allocatively and technically efficient? This report aims to contribute to the policy discussion in Peru about the broad challenges faced by public expenditure. Since the last PER was prepared in 2002, a number of important developments have affected the management of public finances. First, the country has engaged in a decentralization process in which regional and local governments are increasingly assuming responsibilities for public service delivery. Second, as fiscal discipline was successfully restored, the policy focus shifted towards improving the efficiency and quality of public spending; and results-based budgeting has been gradually introduced to support policy and expenditure decisions. In addition, the increase in the level and volatility of the price of minerals has highlighted issues related to natural resource taxation and revenue sharing across different levels of government. This report aims to speak to these issues to help inform the policy debate on public expenditure in Peru.